IMPLEMENTASI MODEL PREDIKSI JUMLAH CALON SANTRI PADA SISTEM PENERIMAAN SANTRI BARU - Hafidz Sanjaya; Fajar Maula Hidayat; Dwi Purnomo; Heri Wiranto (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2025)
This community service program was conducted to address the need of Pondok Pesantren At-Tadzkir Maja for a more effective planning mechanism regarding the number of new student applicants, which previously lacked a data-driven prediction system. The purpose of this program is to implement a prediction model for forecasting the number of prospective students by utilizing the Prophet algorithm developed in prior research, and to provide an accessible predictive dashboard for operational use by the institution. The implementation involved needs assessment, model integration into the online admission system, dashboard development, user training, and evaluation of the administrators’ understanding. The results indicate that the model runs automatically and produces informative daily forecasts, while the dashboard enables administrators to interpret trend and seasonal patterns to support capacity planning and admission strategies. The program concludes that the implementation successfully improves the pesantren’s ability to make data-driven decisions, and it is recommended that future work integrates additional external variables and ensures regular model updates to maintain predictive accuracy.